2004
DOI: 10.1038/nm1052
|View full text |Cite
|
Sign up to set email alerts
|

mTOR inhibition reverses Akt-dependent prostate intraepithelial neoplasia through regulation of apoptotic and HIF-1-dependent pathways

Abstract: Loss of PTEN function leads to activation of phosphoinositide 3-kinase (PI3K) signaling and Akt. Clinical trials are now testing whether mammalian target of rapamycin (mTOR) inhibition is useful in treating PTEN-null cancers. Here, we report that mTOR inhibition induced apoptosis of epithelial cells and the complete reversal of a neoplastic phenotype in the prostate of mice expressing human AKT1 in the ventral prostate. Induction of cell death required the mitochondrial pathway, as prostate-specific coexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
668
1
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 896 publications
(714 citation statements)
references
References 37 publications
31
668
1
6
Order By: Relevance
“…mTOR inhibitors induce apoptosis in some types of tumor cells (Hosoi et al, 1999;Nepomuceno et al, 2003;Majumder et al, 2004;Avellino et al, 2005), whereas they trigger autophagy in other settings (Noda and Ohsumi, 1998;Gutierrez et al, 2004;Kanazawa et al, 2004;Ravikumar et al, 2004) as well as in malignant glioma cells as shown in this study and our previous investigation (Takeuchi et al, 2005). Autophagy is a process by which cells degrade and recycle proteins and intracellular components in response to stress or starvation (Klionsky and Emr, 2000;Levine and Klionsky, 2004;Shintani and Klionsky, 2004).…”
Section: Discussionsupporting
confidence: 67%
“…mTOR inhibitors induce apoptosis in some types of tumor cells (Hosoi et al, 1999;Nepomuceno et al, 2003;Majumder et al, 2004;Avellino et al, 2005), whereas they trigger autophagy in other settings (Noda and Ohsumi, 1998;Gutierrez et al, 2004;Kanazawa et al, 2004;Ravikumar et al, 2004) as well as in malignant glioma cells as shown in this study and our previous investigation (Takeuchi et al, 2005). Autophagy is a process by which cells degrade and recycle proteins and intracellular components in response to stress or starvation (Klionsky and Emr, 2000;Levine and Klionsky, 2004;Shintani and Klionsky, 2004).…”
Section: Discussionsupporting
confidence: 67%
“…In the study by Majumder et al (2004), a probasin promoter-myr-HA-AKT1 transgene was used to direct production of activated Akt1 spatially restricted to the luminal epithelial cells of the mouse ventral prostrate (AKT1-Tg). The AKT1-Tg mice developed a highly penetrant prostatic intraepithelial neoplasia (PIN) phenotype.…”
Section: A Gene Expression Signature Of Akt Overexpression In a Transmentioning
confidence: 99%
“…This PIN phenotype was completely dependent on mTOR activation, as treatment with mTOR inhibitor RAD001 induced apoptosis and reversed the PIN phenotype within 2 weeks. To identify genes altered by Akt expression and by subsequent mTOR inhibition, Majumder et al (2004) prepared total RNA after 12 or 48 h of RAD001 or placebo treatment in wild-type and AKT1-Tg mouse prostate, and message abundance was determined for over 20 000 genes using microarrays. From this expression profile data set, it was determined that gene targets of mTOR inhibition were enriched for Hif-1 targets and glycolysis genes (Majumder et al, 2004).…”
Section: A Gene Expression Signature Of Akt Overexpression In a Transmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyruvate kinase (PK) regulates the final rate‐limiting step of glycolysis and catalyses the transfer of a phosphate group from phosphoenolpyruvate (PEP) to adenosine diphosphate 14. This transfer yields one molecule each of pyruvate and adenosine triphosphate 15, 16. PKM1, PKM2, PKL and PKR are PK isoforms expressed in different types of mammalian cells and tissues.…”
Section: Introductionmentioning
confidence: 99%